Due diligence obligations in international human rights law / Maria Monnheimer, Ludwig Maximilian University of Munich. - Monnheimer, Maria, 1988- (Cambridge University Press, 2021)
With the importance of non-State actors ever increasing, the traditional State-centric approach of international law is being put to the test. In particular, significant accountability lacunae have emerged in the field of human rights protection. To address these challenges, this book makes a case for extraterritorial due diligence obligations of States in international human rights law. It traces back how due diligence obligations evolved on the international plane and develops a general analytical framework making the broad and vague notion of due diligence more approachable. The framework is applied to different fields of international law which provides guidance on how due diligence obligations can be better conceptualized. Drawing inspiration from these developments, the book analyses how extraterritorial human rights due diligence obligations could operate in practice and foster global human rights protection.